Differential Plant Growth Promotion Under Reduced Phosphate Rates in Two Genotypes of Maize by a Rhizobial Phosphate-Solubilizing Strain - Beltran-Medina, Jose I.; Romero-Perdomo, Felipe; Molano-Chavez, Lady; Silva, Antonio M. M.; Estrada-Bonilla, German A. (Frontiers in Sustainable Food Systems, 2022)
The biotechnological manipulation of phosphate solubilizing bacteria (PSB) is gaining prominence to improve the poor phosphorus (P) availability in the soil and maintain crop yields. In the present study, we investigated how Rhizobium sp. B02 inoculation influences maize crop development and whether its use reduces phosphate fertilizer rates. We conducted growth promotion assays using P fertilizer doses in two maize genotypes under greenhouse conditions. Morphometric, physiological, and productivity parameters were assessed in three phenological stages: tillering (V5), tassel (VT), and maturity (R6). Maize response was significantly influenced by both inoculation and plant genotype, showing that the plant-promoting effect of inoculation is substantially more prominent in the white endosperm than in the yellow endosperm maize genotype. The development of maize in all phenological stages was promoted by inoculation with Rhizobium sp. B02. The most significant influence of inoculation was observed on shoot dry weight, relative chlorophyll content, shoot P concentration, leaf area, photosynthetic rate, 1000-grain weight, and grain yield. A 17% gain in grain yield, representing 20 g plant-1, was obtained by inoculation with 50% diammonium phosphate (DAP) compared with the control treatment at the same dose. The complete fertilization control was phenocopied by the white endosperm inoculated at 50% DAP in all productivity parameters. Therefore, half of the P fertilization in white endosperm was replaced by inoculation with Rhizobium sp. B02. Herein, we report the potential of this Rhizobium strain in a non-legume crop to improve P management